2020
DOI: 10.1002/adbi.202000117
|View full text |Cite
|
Sign up to set email alerts
|

Interfacing Neurons with Nanostructured Electrodes Modulates Synaptic Circuit Features

Abstract: Understanding neural physiopathology requires advances in nanotechnology‐based interfaces, engineered to monitor the functional state of mammalian nervous cells. Such interfaces typically contain nanometer‐size features for stimulation and recording as in cell‐non‐invasive extracellular microelectrode arrays. In such devices, it turns crucial to understand specific interactions of neural cells with physicochemical features of electrodes, which could be designed to optimize performance. Herein, versatile flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…They showed that nanostructured platinum coatings of neuroelectrodes, as well as unstructured surfaces, do not exhibit cytotoxic effects on the SH-SY5Y cells. Dominguez-Bajo et al [62] grew neuronal cells derived from rats on both flat and nanostructured nickel and gold electrodes. Increased neural cell survival, improved neuronal differentiation, and fewer glial cells were measurable on nanostructured nickel in comparison to its flat counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that nanostructured platinum coatings of neuroelectrodes, as well as unstructured surfaces, do not exhibit cytotoxic effects on the SH-SY5Y cells. Dominguez-Bajo et al [62] grew neuronal cells derived from rats on both flat and nanostructured nickel and gold electrodes. Increased neural cell survival, improved neuronal differentiation, and fewer glial cells were measurable on nanostructured nickel in comparison to its flat counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the sharp and patch-clamp electrodes, the noninvasive extracellular techniques enable the simultaneous recording and stimulation of electrogenic cells over long time periods without mechanically damaging the cell membrane. [12,13,14] c) Macroscale measurement of wide areas brain's activities: [15] This method can be used to examine the functional connectivity of different regions in the brain, but with a lower spatial resolution. Accordingly, micro-and mesoscale extracellular recording sensors possess the greatest potential to facilitate simultaneous, multisite, long-term, and multiscale in vitro and in vivo recording from large populations of neurons.…”
Section: Introductionmentioning
confidence: 99%
“…The latter was obtained drilling an 8 mm‐diameter hole in the bottom of a 35 mm PS petri dish (Falcon). [ 42 ] To ensure neuronal viability and avoid medium leak during culture the sample assembly was mounted on the petri dish hole using PDMS silicone elastomer (Sylgard 184, Dow Corning Co.). [ 37 ] This assembly offered easy access for the stimulating electrode to contact in a dry environment the PS‐CNT NPs from the bottom side (see the sketch in Figure 5A).…”
Section: Methodsmentioning
confidence: 99%